2021
DOI: 10.1093/bioinformatics/btab859
|View full text |Cite
|
Sign up to set email alerts
|

DeepSVP: integration of genotype and phenotype for structural variant prioritization using deep learning

Abstract: Motivation Structural genomic variants account for much of human variability and are involved in several diseases. Structural variants are complex and may affect coding regions of multiple genes, or affect the functions of genomic regions in different ways from single nucleotide variants. Interpreting the phenotypic consequences of structural variants relies on information about gene functions, haploinsufficiency or triplosensitivity, and other genomic features. Phenotype-based methods to ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Geneticists are now using deep learning approaches to efficiently identify quantitative trait loci and single nucleotide polymorphisms for thousands of emergent phenotypes, both physiological and behavioral. For example, DeepSVP is a deep learning algorithm that leverages genomic information obtained in ontologies and phenotypes obtained in mouse loss-of-function studies to accurately predict whether a structural variant in the human genome will be pathogenic ( Althagafi et al, 2021 ). Table 5 summarizes different, novel deep learning methods that are being used to characterize phenotypes based on genetics and morphology, in addition to behavior.…”
Section: Advances In the Analysis Of Behavioral Neurosciencementioning
confidence: 99%
“…Geneticists are now using deep learning approaches to efficiently identify quantitative trait loci and single nucleotide polymorphisms for thousands of emergent phenotypes, both physiological and behavioral. For example, DeepSVP is a deep learning algorithm that leverages genomic information obtained in ontologies and phenotypes obtained in mouse loss-of-function studies to accurately predict whether a structural variant in the human genome will be pathogenic ( Althagafi et al, 2021 ). Table 5 summarizes different, novel deep learning methods that are being used to characterize phenotypes based on genetics and morphology, in addition to behavior.…”
Section: Advances In the Analysis Of Behavioral Neurosciencementioning
confidence: 99%
“…Another tool, SVpath, predicts the pathogenicity of exonic SVs by incorporating features that are based on functional impact scores of overlapping SNVs, as well as gene level and transcriptomics scores [ 15 ]. Developing this approach further, DeepSVP integrates ranking of noncoding variants and incorporates phenotype information using a deep learning approach to improve the selection of patient-specific variants in a more precise manner [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…15 Developing this approach further, DeepSVP integrates ranking of noncoding variants and incorporates phenotype information using a deep learning approach to improve the selection of patient-specific variants in a more precise manner. 16 In the field of TRs, efforts to prioritize variants have focused on an underlying assumption that TR constraint correlates with pathogenicity. Gymrek et al showed this to be true for select early-onset disease loci such as RUNX2 and HOXD13.…”
Section: Introductionmentioning
confidence: 99%
“…15 Developing this approach further, DeepSVP integrates ranking of noncoding variants and incorporates phenotype information using a deep learning approach to improve the selection of patient-specific variants in a more precise manner. 16…”
Section: Introductionmentioning
confidence: 99%